Banks, markets, and financial stability - Armin Eder; Falko Fecht; Thilo Pausch (Deutsche Bundesbank, 2014)
We use a Diamond/Dybvig-based model with two banks operating in separate regions connected by a common asset market in which banks and sophisticated depositors invest. We study the effect of a potential run (crisis) and subsequent fire sales on the asset price in both the crisis and no-crisis state. In our model, the two are jointly determined by a cash-in-the-market pricing and a no-arbitrage condition. We find that (i) a higher crisis probability increases the liquidity premium and thus asset prices in the normal and crisis case and (ii) a higher share of sophisticated investors increases market depth and thus the crisis price while it might also raise the asset price in the normal state.
Keywords: G21; G23; G12; 330; liquidity risk; financial crises; contagion; asset price bubbles